2021
DOI: 10.1097/rct.0000000000001246
|View full text |Cite
|
Sign up to set email alerts
|

Spindle Cell Carcinoma of the Breast: Investigation of Magnetic Resonance Imaging Features of 26 Cases

Abstract: The aim of the study was to retrospectively investigate the fatsaturated T2-weighted sequences (FST2WI) and 3-dimensional dynamic contrast-enhanced sequence (DCE) of magnetic resonance imaging (MRI) findings of breast spindle cell carcinoma (SpCC).Methods: Twenty-six women with surgically confirmed breast SpCC, who underwent breast MRI in 2 institutions, were enrolled in this study (mean age, 54 years; range, 27-81 years). Two breast radiologists determined the MRI findings by consensus after independent inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Spindle cell carcinoma of the breast is a rare, aggressive form of breast cancer that accounts for 0.02-0.5% of all cases of invasive breast cancer in women [ 4 ]. Due to the aggressive nature of the disease, prompt diagnosis and treatment is necessary to achieve optimal outcomes for patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Spindle cell carcinoma of the breast is a rare, aggressive form of breast cancer that accounts for 0.02-0.5% of all cases of invasive breast cancer in women [ 4 ]. Due to the aggressive nature of the disease, prompt diagnosis and treatment is necessary to achieve optimal outcomes for patients.…”
Section: Discussionmentioning
confidence: 99%
“…The MRI findings of spindle cell carcinoma of the breast were detailed in a series of 26 cases reported by Tokuda et al [ 4 ]. In this study, several radiologic features were common across the cases reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations